Predictors of adverse outcome in the first and second waves of the COVID-19 pandemic: results from a UK centre. (January 2022) - Martin, Christopher A.; Pan, Daniel; Hills, George; Modha, Deborah; Patel, Prashanth; Gray, Laura J.; Jenkins, David R.; Barton, Linda; Jones, William; Brunskill, Nigel J.; Haldar, Pranab; Khunti, Kamlesh; et al.
Background/Aims: Data concerning differences in demographics/disease severity between the first and second waves of COVID-19 are limited. We aimed to examine prognosis in patients presenting to hospital with COVID-19 amongst different ethnic groups between the first and second waves in the UK.Methods: In this retrospective cohort study, we included 1763 patients presenting to a regional hospital centre in Leicester (UK) and compared those in the first ( n  = 956) and second ( n  = 807) waves. Admission National Early Warning Scores, mechanical ventilation and mortality rate were lower in the second wave compared with the first.Results: Thirty-day mortality risk in second wave patients was approximately half that of first wave patients [adjusted hazard ratio (aHR) 0.55, 95% confidence interval (CI) 0.40–0.75]. In the second wave, Black patients were at higher risk of 30-day mortality than White patients (4.73, 1.56–14.3). Conclusion: We found that disporportionately higher risks of death in patients from ethnic minority groups were not equivalent across consecutive waves of the pandemic. This suggests that risk factors for death in those from ethnic minority groups are malleable and potentially reversible. Our findings need urgent investigation in larger studies.